Validación de la propuesta pedagógica para la formación investigativa de los estudiantes de licenciatura en Educación Física, Recreación y Deporte (2010)
ABSTRACT: This research report accounts for the process of research training of graduates in Physical Education, for the Graduate Program in Basic Education, with emphasis on Physical Education, Recreation and Sport offered by Politécnico Colombiano Jaime Isaza Cadavid. To solve this problem, a teaching strategy was designed and implemented focusing on three areas: the career’s curriculum, including research workshops every period with increasing complexity; extra-curricular activities involving students in a learning community, participation in projects and events, and faculty training and self-improvement as a requirement to give continuity to the strategy that was validated in that context. In general, the research process allowed for giving ground and designing the teaching strategy as a viable solution to address the requirements of the National Accreditation Council concerning teacher training quality accreditation proccesses for education programs in Colombia.